SiBCN ceramic slurry for direct-writing 3D printing and preparation method and printing method of SiBCN ceramic slurry
By using SiBCN ceramic slurry with components such as cured polyborosilazane PBSZ powder and inorganic rheology additives, combined with 3D printing technology, the problems of complex molding and internal structure optimization design of SiBCN ceramics are solved, and high density and good dispersion ceramic materials are achieved, which improves flexural strength and moldability, and reduces costs.
Patent Information
- Application Number
- CN202411808826.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-12-10
AI Technical Summary
In the prior art, the selection and dispersion of precursor fillers of SiBCN ceramics are uneven, which makes it difficult to achieve complex molding of ceramics and optimized internal structure design.
The cured polyborosilazane PBSZ powder is used as a filler, combined with inorganic rheology additives and rheology synergists, to adjust the viscosity and rheology characteristics of the slurry, and the complex structural molding of SiBCN ceramics is achieved through 3D printing technology.
The high density and good dispersion of SiBCN ceramics are achieved, the flexural strength and moldability of the ceramics are improved, the cost is reduced, and complex components can be flexibly prepared.
Smart Images

Figure CN119638443A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of ceramic additive manufacturing. Background Art
[0002] Real-time detection of internal pressure and temperature of aviation turbine engines helps to understand the operation of the engine and improve its operating efficiency. As a new type of multi-component silicon-based ceramic, SiBCN has higher thermal stability and better mechanical properties, showing great application potential. If it is applied to engine sensors, the working stability of the sensor can be improved. Based on the application requirements of sensors, traditional preparation methods are difficult to achieve complex molding of SiBCN ceramics and optimized design of internal structures. Combining SiBCN precursors with 3D printing technology, by regulating the rheological properties of slurry, complex structural molding of SiBCN ceramics can be achieved, thereby further expanding its application range. However, based on the chemical sensitivity of the precursor, the selection of fillers is a major problem. The precursor is highly active and easily reacts with chemical additives. For SiBCN ceramics, in order to obtain ceramics with high purity and good performance, the environmental factors of the precursor during the experiment must be strictly controlled. Although inorganic fillers do not affect the properties of the precursor, there are differences in chemical and physical properties between them and organic precursors, and they may not be well dispersed. Therefore, the selection of fillers is a difficult problem and is also a crucial link to ensure the final good performance of ceramics. Summary of the invention
[0003] The present invention aims to solve the problems of SiBCN precursor filler selection and uneven dispersion in existing direct writing printing, and further provide a SiBCN ceramic slurry for direct writing 3D printing and a preparation method and a printing method thereof.
[0004] A SiBCN ceramic slurry for direct writing 3D printing is prepared by 20% to 45% of solidified polyborosilazane PBSZ powder, 3% to 6% of an inorganic rheological additive, 0% to 2% of a rheological enhancer and the remainder of polyborosilazane PBSZ liquid in terms of mass percentage.
[0005] A method for preparing SiBCN ceramic slurry for direct writing 3D printing is carried out according to the following steps:
[0006] 1. Polyborosilazane PBSZ curing:
[0007] In a nitrogen atmosphere at a temperature of 200° C. to 500° C., the polyborosilazane PBSZ liquid is cured for 1 h to 4 h, and then cooled in the furnace to obtain a cured precursor;
[0008] 2. Ball mill crushing:
[0009] The solidified precursor is ball-milled and sieved to obtain solidified polyborosilazane PBSZ powder;
[0010] 3. Weighing:
[0011] Weigh 20% to 45% of the cured polyborosilazane PBSZ powder, 3% to 6% of the inorganic rheological additive, 0% to 2% of the rheological enhancer and the balance of polyborosilazane PBSZ liquid according to mass percentage;
[0012] 4. Slurry preparation:
[0013] The weighed solidified polyborosilazane PBSZ powder is added to the polyborosilazane PBSZ liquid and subjected to vacuum degassing treatment, and then an inorganic rheological additive is added and subjected to vacuum degassing treatment, and finally a rheological enhancer is added and subjected to vacuum degassing treatment to obtain SiBCN ceramic slurry for direct writing 3D printing.
[0014] A method for printing SiBCN ceramic slurry for direct writing 3D printing is carried out according to the following steps:
[0015] 1. Direct writing 3D printing SiBCN ceramic slurry is introduced into the printing syringe for degassing, and then printed under the conditions of line spacing of 0.48mm-0.54mm, printing layer thickness of 0.50mm-0.60mm, pressure of 45Psi-75Psi, printing speed of 5mm / min-15mm / min and printing nozzle size of 400μm-800μm to obtain a printed blank;
[0016] 2. Solidify and sinter the printed blank to obtain SiBCN ceramic structural parts.
[0017] The beneficial effects of the present invention are:
[0018] The present invention uses the solidified precursor powder as filler, which is homologous to the polyborosilazane PBSZ liquid and is used to adjust the viscosity of the slurry. While playing a supporting role, the two shrink synchronously during the sintering process, which can achieve better bonding and improve the density of the ceramic; the inorganic rheological additive can increase the network structure of the liquid molecules, prevent sedimentation, and improve the elasticity of the slurry; the use of the rheological enhancer can maximize the efficacy of the rheological additive.
[0019] The slurry prepared by this method can ensure the density and dispersion of ceramic materials, and has a fast printing speed and high material utilization rate, which greatly reduces the cost. The final ceramic bending strength can reach more than 90MPa, the density can be more than 95%, the formability is good, and the required size and shape can be flexibly prepared to obtain the required complex components. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 These are photos of the SiBCN ceramic structure printed in Example 1 before and after sintering, a is after curing and before sintering, and b is after curing and sintering;
[0021] Figure 2 Rheological curves of SiBCN ceramic slurry for direct writing 3D printing prepared in Examples 1 to 2 and Comparative Experiments 1 to 2, (a) viscosity curve, (b) stress curve;
[0022] Figure 3 XRD patterns of SiBCN ceramic structural parts printed in Examples 1 to 2 and Comparative Experiments 1 to 2;
[0023] Figure 4 These are the fracture morphologies of SiBCN ceramic structural components printed in Examples 1 to 2 and Comparative Experiments 1 to 2, a) Comparative Experiment 1, b) Example 1, c) Example 2, d) Comparative Experiment 2. DETAILED DESCRIPTION
[0024] Specific implementation method 1: This implementation method is a SiBCN ceramic slurry for direct writing 3D printing, which is prepared by 20% to 45% of cured polyborosilazane PBSZ powder, 3% to 6% of inorganic rheological additives, 0% to 2% of rheological enhancers and the remainder of polyborosilazane PBSZ liquid in mass percentage.
[0025] The beneficial effects of this embodiment are:
[0026] This embodiment uses the solidified precursor powder as filler, which is homologous to the polyborosilazane PBSZ liquid and is used to adjust the viscosity of the slurry. While playing a supporting role, the two shrink synchronously during the sintering process, which can achieve better bonding and improve the density of the ceramic; the inorganic rheological additive can increase the network structure of the liquid molecules, prevent sedimentation, and improve the elasticity of the slurry; the use of a rheological enhancer can maximize the effectiveness of the rheological additive.
[0027] The slurry prepared by this method can ensure the density and dispersion of ceramic materials, and has a fast printing speed and high material utilization rate, which greatly reduces the cost. The final ceramic bending strength can reach more than 90MPa, the density can be more than 95%, the formability is good, and the required size and shape can be flexibly prepared to obtain the required complex components.
[0028] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the inorganic rheological additive is one or a combination of nanoclay, gas phase SiO2 and organic modified sheet silicate. Other aspects are the same as specific embodiment 1.
[0029] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that the SiBCN ceramic slurry for direct writing 3D printing is a gel-like fluid with shear-thinning properties. -1Under the condition of , the viscosity is 1400Pa·s to 3000Pa·s. Others are the same as the first or second specific implementation.
[0030] Specific embodiment 4: This embodiment is a method for preparing SiBCN ceramic slurry for direct writing 3D printing, which is characterized by being carried out according to the following steps:
[0031] 1. Polyborosilazane PBSZ curing:
[0032] In a nitrogen atmosphere at a temperature of 200° C. to 500° C., the polyborosilazane PBSZ liquid is cured for 1 h to 4 h, and then cooled in the furnace to obtain a cured precursor;
[0033] 2. Ball mill crushing:
[0034] The solidified precursor is ball-milled and sieved to obtain solidified polyborosilazane PBSZ powder;
[0035] 3. Weighing:
[0036] Weigh 20% to 45% of the cured polyborosilazane PBSZ powder, 3% to 6% of the inorganic rheological additive, 0% to 2% of the rheological enhancer and the balance of polyborosilazane PBSZ liquid according to mass percentage;
[0037] 4. Slurry preparation:
[0038] The weighed solidified polyborosilazane PBSZ powder is added to the polyborosilazane PBSZ liquid and subjected to vacuum degassing treatment, and then an inorganic rheological additive is added and subjected to vacuum degassing treatment, and finally a rheological enhancer is added and subjected to vacuum degassing treatment to obtain SiBCN ceramic slurry for direct writing 3D printing.
[0039] Specific embodiment 5: This embodiment is different from specific embodiment 4 in that the number average molecular weight of the polyborosilazane PBSZ liquid described in step 1 and step 3 is 600-800, and the viscosity is 8000cp-20000cp. Others are the same as specific embodiment 4.
[0040] Specific embodiment 6: This embodiment differs from specific embodiment 4 or 5 in that: in step 1, the temperature of the polyborosilazane PBSZ liquid is raised to 200° C. to 500° C. at a heating rate of 1° C. / min to 3° C. / min under a nitrogen atmosphere. The rest is the same as specific embodiment 4 or 5.
[0041] Specific embodiment 7: This embodiment is different from Specific embodiments 4 to 6 in that: the ball milling crushing described in step 2 is specifically carried out for 2h to 6h at a ball milling speed of 200r / min to 300r / min and a ball-to-material mass ratio of (10 to 20):1; the particle size of the cured polyborosilazane PBSZ powder prepared in step 2 is 5μm to 20μm. Others are the same as Specific embodiments 4 to 6.
[0042] Specific embodiment eight: This embodiment is different from specific embodiments four to seven in that the vacuum degassing treatment described in step four is carried out according to the following steps: first, under the conditions of a vacuum degree of 90kPa to 102kPa and a rotation speed of 1500r / min to 2000r / min, vacuum degassing for 60s to 120s, then under the conditions of a vacuum degree of 50kPa to 70kPa and a rotation speed of 2000r / min to 2500r / min, vacuum degassing for 100s to 200s, and then under the conditions of a vacuum degree of 30kPa to 50kPa and a rotation speed of 1000r / min to 2000r / min, vacuum degassing for 60s to 120s. The rest is the same as specific embodiments four to seven.
[0043] Specific embodiment 9: This embodiment is a method for printing SiBCN ceramic slurry for direct writing 3D printing, which is carried out according to the following steps:
[0044] 1. Direct writing 3D printing SiBCN ceramic slurry is introduced into the printing syringe for degassing, and then printed under the conditions of line spacing of 0.48mm-0.54mm, printing layer thickness of 0.50mm-0.60mm, pressure of 45Psi-75Psi, printing speed of 5mm / min-15mm / min and printing nozzle size of 400μm-800μm to obtain a printed blank;
[0045] 2. Solidify and sinter the printed blank to obtain SiBCN ceramic structural parts.
[0046] Specific embodiment 10: This embodiment differs from specific embodiment 9 in that: the degassing described in step 1 is specifically performed at a rotation speed of 2000r / min to 2500r / min for 60s to 120s; the curing described in step 2 is specifically performed at a heating rate of 1°C / min to 2°C / min to 120°C to 160°C in a nitrogen atmosphere, and then cured for 1h to 4h in a nitrogen atmosphere and at a temperature of 120°C to 160°C; the sintering described in step 2 is specifically performed at a heating rate of 0.5°C / min to 1.5°C / min to 900°C to 1500°C in a nitrogen atmosphere, and then sintered for 1h to 4h in a nitrogen atmosphere and at a temperature of 900°C to 1500°C. The rest is the same as specific embodiment 9.
[0047] The following examples are used to verify the beneficial effects of the present invention:
[0048] Embodiment 1:
[0049] A method for preparing SiBCN ceramic slurry for direct writing 3D printing is carried out according to the following steps:
[0050] 1. Polyborosilazane PBSZ curing:
[0051] In a nitrogen atmosphere, the polyborosilazane PBSZ liquid is heated to 400°C at a heating rate of 1°C / min, and then the polyborosilazane PBSZ liquid is cured for 3 hours in a nitrogen atmosphere at a temperature of 400°C, and then cooled in the furnace to obtain a cured precursor;
[0052] 2. Ball mill crushing:
[0053] Under the conditions of a ball milling speed of 300 r / min and a ball-to-material mass ratio of 10:1, the solidified precursor was ball milled for 4 hours, and then passed through a 100-mesh sieve to obtain a solidified polyborosilazane PBSZ powder;
[0054] The particle size of the cured polyborosilazane PBSZ powder is 5 μm to 20 μm;
[0055] 3. Weighing:
[0056] Weigh 28% of the cured polyborosilazane PBSZ powder, 6% of the inorganic rheological additive and the balance of polyborosilazane PBSZ liquid according to mass percentage;
[0057] The inorganic rheological additive is gas-phase SiO2, and the manufacturer purchased is Hubei Huifu Nanomaterial Co., Ltd.;
[0058] 4. Slurry preparation:
[0059] The weighed solidified polyborosilazane PBSZ powder is added to the polyborosilazane PBSZ liquid and subjected to vacuum degassing, and then an inorganic rheological additive is added and subjected to vacuum degassing, and finally a rheological enhancer is added and subjected to vacuum degassing to obtain SiBCN ceramic slurry for direct writing 3D printing, which is named 28% 400℃+6% SiO2;
[0060] The vacuum degassing treatment is carried out according to the following steps: first, vacuum degassing for 90 seconds at a vacuum degree of 100 kPa and a rotation speed of 2000 r / min, then vacuum degassing for 180 seconds at a vacuum degree of 50 kPa and a rotation speed of 2500 r / min, and then vacuum degassing for 90 seconds at a vacuum degree of 35 kPa and a rotation speed of 1500 r / min;
[0061] The SiBCN ceramic slurry for direct writing 3D printing is a gel-like fluid with shear thinning properties. -1 Under the conditions of , the viscosity is 1400Pa·s~1500Pa·s.
[0062] The number average molecular weight of the polyborosilazane PBSZ liquid described in step 1 and step 3 is 600-800, and the viscosity is 8000cp-20000cp.
[0063] The printing method of the SiBCN ceramic slurry for direct writing 3D printing prepared above is carried out according to the following steps:
[0064] 1. Direct writing 3D printing SiBCN ceramic slurry was introduced into the printing syringe for degassing, and then printed under the conditions of line spacing of 0.54 mm, printing layer thickness of 0.56 mm, pressure of 55 Psi, printing speed of 9 mm / min and printing nozzle size of 600 μm to obtain a printed blank;
[0065] 2. Solidify and sinter the printed blank to obtain SiBCN ceramic structural parts.
[0066] The degassing described in step 1 is specifically to degas for 100s at a rotation speed of 2500r / min; the curing described in step 2 is specifically to heat the temperature to 150°C at a heating rate of 1°C / min in a nitrogen atmosphere, and then to cure for 1h in a nitrogen atmosphere and a temperature of 150°C; the sintering described in step 2 is specifically to heat the temperature to 1000°C at a heating rate of 0.5°C / min in a nitrogen atmosphere, and then to sinter for 2h in a nitrogen atmosphere and a temperature of 1000°C.
[0067] Embodiment 2: This embodiment differs from the specific embodiment 1 in that: in the preparation method: in step 1, under a nitrogen atmosphere, the polyborosilazane PBSZ liquid is heated to 500°C at a heating rate of 1°C / min, and then the polyborosilazane PBSZ liquid is cured for 3 hours under a nitrogen atmosphere and a temperature of 500°C; in step 3, 40% of the cured polyborosilazane PBSZ powder, 6% of the inorganic rheological additive and the remainder of the polyborosilazane PBSZ liquid are weighed by mass percentage; in step 4, the SiBCN ceramic slurry for direct writing 3D printing described in step 4 is a gel-like fluid with shear thinning properties, and at a shear rate of 1s -1 Under the condition of , the viscosity is 2300Pa·s~2500Pa·s; the SiBCN ceramic slurry for direct writing 3D printing prepared in step 4 is named 40%500℃+6%SiO2. In the printing method: the pressure is 60Psi, and the printing speed is 8mm / min. The rest is the same as the specific implementation method 1.
[0068] Comparative experiment 1: The difference between this embodiment and specific embodiment 1 is that: in the preparation method: in step 1, under a nitrogen atmosphere, the polyborosilazane PBSZ liquid is heated to 160°C at a heating rate of 1°C / min, and then the polyborosilazane PBSZ liquid is cured for 3 hours under a nitrogen atmosphere and a temperature of 160°C; in step 3, 40% of the cured polyborosilazane PBSZ powder, 6% of the inorganic rheological additive and the remainder of the polyborosilazane PBSZ liquid are weighed by mass percentage; the SiBCN ceramic slurry for direct writing 3D printing described in step 4 is a gel-like fluid with shear thinning properties, which can be cured at a shear rate of 1s -1 Under the condition of , the viscosity is 1400Pa·s-1600Pa·s; the SiBCN ceramic slurry for direct writing 3D printing prepared in step 4 is named 40% 160℃+6% SiO2. The rest is the same as the first embodiment.
[0069] Comparative experiment 2: The difference between this embodiment and specific embodiment 1 is that: in the preparation method: in step 1, under a nitrogen atmosphere, the polyborosilazane PBSZ liquid is heated to 1000°C at a heating rate of 1°C / min, and then the polyborosilazane PBSZ liquid is cured for 3 hours under a nitrogen atmosphere and a temperature of 1000°C; in step 3, 40% of the cured polyborosilazane PBSZ powder, 9% of the inorganic rheological additive and the remainder of the polyborosilazane PBSZ liquid are weighed by mass percentage; the SiBCN ceramic slurry for direct writing 3D printing described in step 4 is a gel-like fluid with shear thinning properties, which can be easily deformed at a shear rate of 1s -1 Under the condition of , the viscosity is 2400Pa·s~2600Pa·s; the SiBCN ceramic slurry for direct writing 3D printing prepared in step 4 is named 40% 1000℃+9%SiO2. In the printing method: the pressure is 60Psi and the printing speed is 7mm / min. The rest is the same as the specific implementation method 1.
[0070] Comparative experiment three: The difference between this embodiment and the specific embodiment one is that: in the preparation method: in step one, the polyborosilazane PBSZ liquid is heated to 160°C at a heating rate of 1°C / min under a nitrogen atmosphere, and then the polyborosilazane PBSZ liquid is cured for 3 hours under the conditions of a nitrogen atmosphere and a temperature of 160°C; in step three, 45% of the cured polyborosilazane PBSZ powder and the remaining polyborosilazane PBSZ liquid are weighed by mass percentage. The rest is the same as the specific embodiment one.
[0071] The SiBCN ceramic slurry for direct writing 3D printing prepared in Example 3 is in a viscous gel state, and its rheology does not have shear thinning behavior, indicating that the addition of inorganic rheological additives such as gas-phase SiO2 is beneficial to improving the formability of the slurry.
[0072] Test and calculate according to the three-point test bending formula: Where L is the span (in mm), F is the failure strength (in MPa), h is the thickness (in mm), and b is the width (in mm); the sample printed for performance test is a 6mm×4mm×35mm strip sample, the filling routing method is straight line filling, and the filling rate is 100%. The bending strength of the SiBCN ceramic structure printed in Example 1 is 101.2MPa, and the density is 1.67g / cm 3 The open porosity is 3.4%. The bending strength of the SiBCN ceramic structure printed in Example 2 is 91.2 MPa and the density is 1.61 g / cm 3 , the open porosity is 6.8%. Comparative Experiment 1 The bending strength of the SiBCN ceramic structure printed is 50.8MPa and the density is 1.69g / cm 3 , the open porosity is 2.4%. The strength of the SiBCN ceramic structure printed in the comparative experiment 2 is 20.1MPa and the density is 1.58g / cm 3 , the open porosity is 20.1%.
[0073] Figure 1 The photos of the SiBCN ceramic structure printed in Example 1 before and after sintering, a is after curing and before sintering, b is after curing and sintering; it can be seen from the figure that the slurry can be adjusted to form a complex porous structure. The printing size of the structure is 15×15mm, the height is 5mm, and the printing accuracy is ±10μm. After sintering, the lateral shrinkage rate is 24.3%, and the longitudinal shrinkage rate is 18.8%.
[0074] Figure 2 Rheological curves of SiBCN ceramic slurry for direct writing 3D printing prepared in Examples 1 to 2 and Comparative Experiments 1 to 2, (a) viscosity curve, (b) stress curve; It can be seen from the figure that in each embodiment, the Newtonian fluid can be converted into a non-Newtonian fluid by changing the additive ratio, which enhances the shear thinning behavior and apparent viscosity of the slurry, which indirectly indicates that the slurry has print formability.
[0075] Figure 3 XRD patterns of SiBCN ceramic structural parts printed in Examples 1 to 2 and Comparative Experiments 1 to 2; it can be seen from the figure that the ceramics prepared in Examples 1 to 2 and Comparative Experiment 1 are amorphous structures, and the ceramics prepared in Comparative Experiment 2 have slight crystallization.
[0076] Figure 4The fracture morphology images of SiBCN ceramic structural parts printed for Examples 1 to 2 and Comparative Experiments 1 to 2, a) Comparative Experiment 1, b) Example 1, c) Example 2, d) Comparative Experiment 2. Comparing the ceramic fractures, it can be clearly seen that the ceramic sections prepared in Examples 1 to 2 and Comparative Experiment 1 are relatively dense, and no obvious pores can be seen. There are a large number of pores in the ceramic section prepared in Comparative Experiment 2, which is also the main reason for the performance degradation. This is because the powder preparation temperature of Examples 1 to 2 and Comparative Experiment 1 is below the cracking temperature (900°C), and its property transformation is relatively low, and the similarity with the properties of the organic precursor is high, which makes the powder dispersibility better. As the powder curing temperature increases, its cross-linking degree and properties gradually change to inorganic structures, and organic macromolecules gradually decompose. When the powder temperature is above the cracking temperature, such as in comparative experiment 2, due to the chemical property change brought about by ceramicization, the thermal expansion difference with the precursor increases, the powder dispersibility becomes worse, the slurry extrusion is unstable, and the dispersibility of the powder in the slurry is reduced, resulting in sedimentation during printing, the introduction of a large amount of gas and defects, resulting in increased porosity and decreased strength. In comparative experiment 1, although the obtained ceramic density is higher, its strength is not as good as that of Example 1 and Example 2. This is because the preparation temperature of the filler powder in comparative experiment 1 is 160°C. Compared with Example 1 and Example 2, the cross-linking degree of its precursor is lower, and there are still a large number of low molecular weight organic groups remaining. These organic groups can gradually fill the small pores during the sintering process, thereby forming a relatively dense microstructure; but low temperature curing may lead to an imperfect ceramic network structure and a lack of sufficient cross-linking density, resulting in a lower strength of the ceramic.
Claims
1. A SiBCN ceramic slurry for direct writing 3D printing, characterized in that The invention is prepared from 20% to 45% of solidified polyborosilazane PBSZ powder, 3% to 6% of inorganic rheological additive, 0% to 2% of rheological enhancer and the balance of polyborosilazane PBSZ liquid in terms of mass percentage.
2. The SiBCN ceramic slurry for direct writing 3D printing according to claim 1, characterized in that The inorganic rheological additive is one or a combination of nano clay, gas phase SiO2 and organic modified sheet silicate.
3. The SiBCN ceramic slurry for direct writing 3D printing according to claim 1, characterized in that The SiBCN ceramic slurry for direct writing 3D printing is a gel-like fluid with shear thinning properties. -1 Under the conditions of , the viscosity is 1400Pa·s~3000Pa·s.
4. The method for preparing SiBCN ceramic slurry for direct writing 3D printing according to claim 1, characterized in that It is carried out in the following steps:
1. Polyborosilazane PBSZ curing: In a nitrogen atmosphere at a temperature of 200° C. to 500° C., the polyborosilazane PBSZ liquid is cured for 1 h to 4 h, and then cooled in the furnace to obtain a cured precursor; 2. Ball mill crushing: The solidified precursor is ball-milled and sieved to obtain solidified polyborosilazane PBSZ powder; 3. Weighing: Weigh 20% to 45% of the cured polyborosilazane PBSZ powder, 3% to 6% of the inorganic rheological additive, 0% to 2% of the rheological enhancer and the balance of polyborosilazane PBSZ liquid according to mass percentage; 4. Slurry preparation: The weighed solidified polyborosilazane PBSZ powder is added to the polyborosilazane PBSZ liquid and subjected to vacuum degassing treatment, and then an inorganic rheological additive is added and subjected to vacuum degassing treatment, and finally a rheological enhancer is added and subjected to vacuum degassing treatment to obtain SiBCN ceramic slurry for direct writing 3D printing.
5. The method for preparing SiBCN ceramic slurry for direct writing 3D printing according to claim 4, characterized in that The number average molecular weight of the polyborosilazane PBSZ liquid described in step 1 and step 3 is 600-800, and the viscosity is 8000cp-20000cp.
6. The method for preparing SiBCN ceramic slurry for direct writing 3D printing according to claim 4, characterized in that In step 1, under a nitrogen atmosphere, the temperature of the polyborosilazane PBSZ liquid is raised to 200° C. to 500° C. at a heating rate of 1° C. / min to 3° C. / min.
7. The method for preparing SiBCN ceramic slurry for direct writing 3D printing according to claim 4, characterized in that The ball milling crushing described in step 2 is specifically carried out for 2h to 6h at a ball milling speed of 200r / min to 300r / min and a ball-to-material mass ratio of (10 to 20):1; the particle size of the cured polyborosilazane PBSZ powder prepared in step 2 is 5μm to 20μm.
8. The method for preparing SiBCN ceramic slurry for direct writing 3D printing according to claim 4, characterized in that The vacuum degassing treatment described in step 4 is carried out according to the following steps: first, vacuum degassing for 60s to 120s at a vacuum degree of 90kPa to 102kPa and a rotation speed of 1500r / min to 2000r / min, then vacuum degassing for 100s to 200s at a vacuum degree of 50kPa to 70kPa and a rotation speed of 2000r / min to 2500r / min, and then vacuum degassing for 60s to 120s at a vacuum degree of 30kPa to 50kPa and a rotation speed of 1000r / min to 2000r / min.
9. A method for printing SiBCN ceramic slurry for direct writing 3D printing as claimed in claim 1, characterized in that It is carried out in the following steps:
1. Direct writing 3D printing SiBCN ceramic slurry is introduced into the printing syringe for degassing, and then printed under the conditions of line spacing of 0.48mm-0.54mm, printing layer thickness of 0.50mm-0.60mm, pressure of 45Psi-75Psi, printing speed of 5mm / min-15mm / min and printing nozzle size of 400μm-800μm to obtain a printed blank; 2. Solidify and sinter the printed blank to obtain SiBCN ceramic structural parts.
10. A method for printing SiBCN ceramic slurry for direct writing 3D printing according to claim 9, characterized in that The degassing described in step one is specifically to degas for 60s to 120s at a rotation speed of 2000r / min to 2500r / min; the curing described in step two is specifically to heat the temperature to 120℃ to 160℃ at a heating rate of 1℃ / min to 2℃ / min in a nitrogen atmosphere, and then to cure for 1h to 4h in a nitrogen atmosphere and a temperature of 120℃ to 160℃; the sintering described in step two is specifically to heat the temperature to 900℃ to 1500℃ at a heating rate of 0.5℃ / min to 1.5℃ / min in a nitrogen atmosphere, and then to sinter for 1h to 4h in a nitrogen atmosphere and a temperature of 900℃ to 1500℃.
Citation Information
Patent Citations
Preparation method for compact type carbon-rich precursor ceramic
CN108395256A
Photopolymer resins with solid and liquid phases for polymer-derived ceramics
CN110997760A
Method for preparing ceramic material through ultraviolet light beam synchronous curing assisted direct writing 3D printing
CN113400437A
Method for preparing porous SiOC-based ceramic membrane support by combining laser 3D printing with impregnation cracking process
CN115872771A
Modified SiBCN ceramic material and preparation method thereof
CN116041073A